A rare non-oncological pancreatic mass: eosinophilic pancreatitis diagnosis through EUS-FNA - De Moura, Diogo Turiani Hourneaux; Rocha, Rodrigo Silva de Paula; Jukemura, José; Brunaldi, Vitor Ottoboni; Guedes, Hugo Gonçalo; Torrez, Franz Robert Apodaca; Ribeiro, Igor Braga; Gelrud, Andres; De Moura, Eduardo Guimarães Hourneaux (Endoscopy International Open, 2019)
Background and study aims Eosinophilic pancreatitis (EP) is a rare etiology of chronic pancreatitis, and few cases have been reported. It is characterized by eosinophilic infiltration of the pancreas and elevated IgE levels. EP is difficult to distinguish from pancreatic cancer based on clinical symptoms and auxiliary exams. We present a case of EP and debate the routine performance of endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) for resectable pancreatic mass.